PELATIHAN PEMBUATAN KONTEN VISUAL EDUKATIF MENGGUNAKAN CAPCUT DESKTOP UNTUK MENINGKATKAN LITERASI DIGITAL ANGGOTA RAYON IKSASS SUMATERA PUTRI - Zaehol Fatah; Auliya Auliya (Jurnal Padamu Negeri, 2026)
With the rapid development of digital technology, understanding media literacy, especially in creating educational visual content, is very important. This study aims to evaluate the effectiveness of the CapCut platform as a learning tool to enhance creative skills in video making. The research methods used include theory explanation, device demonstration, intensive guidance, and end-product-based evaluation. The research was conducted at Rayon IKSASS Sumatera Putri. The target of the study were members who had technical issues using CapCut software and had not yet optimised their laptop use for making professional videos with CapCut. The results show that participants' practical skills and innovation increase significantly when they create and develop innovative video content. This study reinforces the conclusion that the CapCut platform is highly relevant as an adaptable and useful learning media.